2022
DOI: 10.3390/v14061314
|View full text |Cite
|
Sign up to set email alerts
|

Virome of Grapevine Germplasm from the Anapa Ampelographic Collection (Russia)

Abstract: Grapevine germplasm collections are unique repositories of grape cultivars; therefore, it is necessary to minimize their infection with pathogens, including viruses, and develop various programs to maintain them in a virus-free state. In our study, we examined the virome of the largest Russian grapevine germplasm collection, the Anapa Ampelographic Collection, using high-throughput sequencing of total RNAs. As a result of bioinformatics analysis and validation of its results by reverse transcription PCR (RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 144 publications
4
30
0
Order By: Relevance
“…The blastn analysis showed that the Russian isolate D1371o had a 79.83% identity at the nucleotide level with an isolate from South Africa (MW309530.1), while the isolate D1357o had an 87.92% identity with a French isolate (MG925333.1). In previous studies, we have also shown a rather low (at the level of 81.41-85.97%) identity of Russian isolates with the world's isolates [30]. On the dendrogram, the Russian GVA isolates were grouped with representative isolates of molecular group I (Supplementary Figure S7), clustering with isolates from France, South Africa and Russia.…”
Section: Grapevine Virus Amentioning
confidence: 60%
See 4 more Smart Citations
“…The blastn analysis showed that the Russian isolate D1371o had a 79.83% identity at the nucleotide level with an isolate from South Africa (MW309530.1), while the isolate D1357o had an 87.92% identity with a French isolate (MG925333.1). In previous studies, we have also shown a rather low (at the level of 81.41-85.97%) identity of Russian isolates with the world's isolates [30]. On the dendrogram, the Russian GVA isolates were grouped with representative isolates of molecular group I (Supplementary Figure S7), clustering with isolates from France, South Africa and Russia.…”
Section: Grapevine Virus Amentioning
confidence: 60%
“…Co-infection of GLRaV-7 with other closteroviruses prevents GLRaV-7 from being identified as the etiological agent of GLRD [67]. GLRaV-1, GLRaV-2, GLRaV-3 and GLRaV-4 have previously been detected in Russia [30,53,54,68,69].…”
Section: Family: Closteroviridaementioning
confidence: 98%
See 3 more Smart Citations